2001
DOI: 10.1073/pnas.061412598
|View full text |Cite
|
Sign up to set email alerts
|

Peyer's patches are required for oral tolerance to proteins

Abstract: To clarify the role of Peyer's patches in oral tolerance induction, BALB͞c mice were treated in utero with lymphotoxin ␤-receptor Ig fusion protein to generate mice lacking Peyer's patches. When these Peyer's patch-null mice were fed 25 mg of ovalbumin (OVA) before systemic immunization, OVA-specific IgG Ab responses in serum and spleen were seen, in marked contrast to low responses in OVA-fed normal mice. Further, high T-cell-proliferative-and delayed-type hypersensitivity responses were seen in Peyer's patch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 44 publications
1
118
2
Order By: Relevance
“…A comparison of the onset of T cell activation in the gutdraining lymphoid tissues with the onset in peripheral non-draining tissues further emphasizes the significance of these tissues in the induction and differentiation of mucosal Tr cells. The active involvement of the draining lymphoid organs confirms earlier reports on the dependency of intact PP and MLN in oral tolerance induction [18,19]. The multiple divisions of the antigen-specific T cells in these locations found within 24-48 h demonstrate that an extremely efficient antigen uptake and presentation process has occurred by this time, most likely by DC residing in the gut epithelium [32].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A comparison of the onset of T cell activation in the gutdraining lymphoid tissues with the onset in peripheral non-draining tissues further emphasizes the significance of these tissues in the induction and differentiation of mucosal Tr cells. The active involvement of the draining lymphoid organs confirms earlier reports on the dependency of intact PP and MLN in oral tolerance induction [18,19]. The multiple divisions of the antigen-specific T cells in these locations found within 24-48 h demonstrate that an extremely efficient antigen uptake and presentation process has occurred by this time, most likely by DC residing in the gut epithelium [32].…”
Section: Discussionsupporting
confidence: 69%
“…We hypothesize that specific conditions in the gut-draining lymphoid tissues are essential for Tr cell induction, as inferred by the finding that oral tolerance is aborted in the absence of mesenteric lymph nodes (MLN) [17], emphasizing the importance of this draining route. Whether the Peyer's patches (PP) are also directly involved in the process is debatable [18][19][20]. That an active response to oral ovalbumin (OVA) occurs in the PP and MLN is revealed by the detection of activated T cells within the first days post-OVA treatment, based on CD69 expression and an increase in T cell number [21].…”
Section: Introductionmentioning
confidence: 99%
“…route, the nose-draining cervical LNs appeared to be the predominant site for tolerance induction (48,49). In models of orally fed Ag, both mesenteric LNs and Peyer's patches were shown to be the predominant sites of Ag presentation (58 -61), and critical for the induction of oral tolerance (59,62). To a lesser extent, oral Ag delivery has also been shown to induce clonal expansion of Ag-specific T cells in the spleen and, in cases in which high doses of Ag are administered, even in peripheral LNs (61,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have suggested that Peyer's patches, which are lymphoid nodules interspersed among the intestinal villi, are essential for mucosal immune responses and oral tolerance to soluble antigens (2,3,10,11). Peyer's patches contain professional antigen-presenting cells (APCs) known as dendritic cells (DCs), which are known to play an important role in both immune responses and immune tolerance in the intestinal mucosa.…”
mentioning
confidence: 99%